Pengaruh Keberadaan Pabrik Kelapa Sawit Pt. Socfindo Terhadap Peningkatan Pendapatan Masyarakat Di Kecamatan Kejuruan Muda Kabupaten Aceh Tamiang - Mustika Khofifah Balqis Lubis; Edi Sofian; Fauzi Fauzi (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
The formulation of the problem in this thesis is whether there is an effect of the existence of a palm oil factory on increasing people's income in the District of Vocational Youth, Aceh Tamiang Regency. This study aims to determine the effect of the existence of a palm oil mill on increasing people's income in the District of Vocational Youth, Aceh Tamiang Regency. The results of this study indicate that there is an influence of the existence of the Palm Oil Mill of PT. Socfindo on increasing people's incomes in the Young Vocational District, Aceh Tamiang Regency, shows that there is a positive influence on the variable existence of the Palm Oil Mill PT. Socfindo (X) on the variable of increasing income. Simultaneously shows that the variable existence of the Palm Oil Mill PT. Socfindo has an effect on increasing people's incomes in the Young Vocational District, Aceh Tamiang Regency.